Ultrasound-guided laser ablation for local control of neck recurrences of medullary thyroid cancer. A feasibility study. (31st December 2018) - Persichetti, Agnese; Bizzarri, Giancarlo; Guglielmi, Rinaldo; Barnabei, Agnese; Bianchini, Antonio; Coccaro, Carmela; Appetecchia, Marialuisa; Papini, Enrico
Abstract: Background : Surgery is the standard treatment for cervical metastases of medullary thyroid cancer (MTC) diagnosed after initial surgical treatment. Repeated neck dissections, however, carry an elevated risk of complications, have an adverse impact on the quality of life, and sometimes do not achieve cure of the disease Clinical case : In a patient who had undergone two cervical neck dissections complicated by accessory nerve injury, an US-guided laser ablation (LA) of a lymph node metastasis of MTC was performed. LA was performed with two treatments during a five month period. The procedure was carried out with one optical fiber and an energy delivery of 3300 and 360 Joules. Treatments were well tolerated and resulted in complete structural and biochemical cure during a 12 month follow-up. No major complication was registered. Conclusions : LA is a promising tool for the management of relapsing cervical metastases that are localized in non- critical areas and are characterized by low progression rate. Advantages of LA are the outpatient setting, the absence of general anesthesia, the tolerability and the safety of the procedure. Thus, LA may be considered as an alternative approach to surgery or active surveillance for the management of local recurrences of MTC in selected patients.